Molecular Docking Senyawa Ekstrak Etanol Daun Kenikir (Cosmos caudatus) Sebagai Inhibitor Il-6 Dalam Respon Inflamasi - Azzahra, Ratu Wifaira; Murdaya, Niky; Al Shofwan, Adnan Aly; Ramadan, Erlangga; Utami, Savira Dwi (Jurnal Farmasi Udayana; Vol. 10, No 2, Tahun 2021, 2021)
Inflammation is the body's natural reaction to protect itself from pathogens that cause disease. Interleukin-6 (IL-6) acts as a pro-inflammatory and anti-inflammatory cytokine released by T cells and macrophages to stimulate an immune response when an infection occurs. In this study, an in silico study of the ethanolic extract of kenikir ( Cosmos caudatus ) leaves as an anti-inflammatory based on its affinity for Interleukin-6 (IL-6) was carried out using the in silico molecular docking method. This research includes simulations of molecular docking of the ethanol extract of kenikir leaves against the IL-6 receptor (PDB ID: 1ALU) and prediction of pharmacokinetic profiles and toxicity using the Pre-ADMET server. The results showed that four potential compounds were obtained, namely C1 ( Kaempferol ), C2 ( 1-Caffeoylquinic acid , C3 ( Procyanidin B1 ), dan C5 ( Quercetin-3-O-pentoside ). The four compounds have better ?G and Ki values ??compared to natural ligands. ?G value; Ki test compounds, namely (-5.29 Kcal / mol; 133.31 uM), (-6.02 Kcal / mol; 38.44 uM), (-5.38 Kcal / mol; 114, 24 uM), and (-5.46 Kcal / mol; 99.50 uM). PreADMET results of the four compounds have good adsorption power so that they can be considered in the preparation of oral route preparations. The results of the Ames test showed that C1 and C2 were mutagenic, while C3 and C4 were non-mutagenic.